Thermal and flow characteristics of alumina nanofluids in microfluidic systems: A low-concentration study - Samylingam, Lingenthiran; Aslfattahi, Navid; Kadirgama, Kumaran; Ramasamy, Devarajan; Kok, Chee Kuang; Norazlianie, Sazali; Wan Sharuzi, Wan Harun; Nor Atiqah, Zolpakar; Mohd Fairusham, Ghazali (Semarak Ilmu Publishing, 2025)
Microfluidic technologies and nanofluids represent a synergistic combination with significant potential for enhancing heat transfer and thermal management applications. This study investigates the thermal and flow characteristics of a 0.001 wt.% alumina (Al₂O₃)-water nanofluid within a custom-designed serpentine microfluidic channel. The nanofluid was prepared and characterized for its thermal conductivity, viscosity, specific heat, and density. Experimental microfluidic studies, supplemented by numerical simulations, were conducted to evaluate the fluid's behavior under controlled conditions. Results indicated a slight increase in thermal conductivity for the Al₂O₃ nanofluid compared to pure water, with increments ranging from 0.16% at 20°C to 0.30% at 80°C, attributed to enhanced Brownian motion of the nanoparticles. Viscosity measurements revealed marginal increases, suggesting minimal impact on fluid flow dynamics. The microfluidic experiments demonstrated a consistent pressure gradient and laminar flow regime, essential for precise control and efficient thermal management. Temperature contours showed effective heat dissipation, with a steady thermal gradient from the inlet to the outlet. The study concludes that low-concentration Al₂O₃ nanofluids can enhance thermal performance in microfluidic systems without significantly affecting flow characteristics, making them suitable for applications requiring efficient heat dissipation, such as electronic cooling and chemical reactions. These findings provide a foundation for future research into higher nanoparticle concentrations and different base fluids, aimed at optimizing the thermal and flow properties of nanofluids in microfluidic environments. The integration of nanofluids with microfluidic technologies holds promise for advancing the performance and reliability of next-generation thermal management systems.